Combined Use of Schizosaccharomyces pombe and a Lachancea thermotolerans Strain with a High Malic Acid Consumption Ability for Wine Production - Vicente Javier; Kelanne Niina; Navascués Eva; Calderón Fernando; Santos Antonio; Marquina Domingo; Yang Baoru; Benito Santiago (MDPI, 2025)
The development of new fermentative strategies exploiting the potential of different wine-related species is of great interest for new winemaking conditions and consumer preferences. One of the most promising non-conventional approaches to wine fermentation is the combined use of deacidifying and acidifying yeasts. Lachancea thermotolerans shows several other properties besides lactic acid production; among them, high malic acid consumption is of great interest in the production of red wines for avoiding undesirable refermentations once bottled. The combination of a L. thermotolerans strain that is able to consume malic acid with a Schizosaccharomyces pombe strain helps to ensure malic acid elimination during alcoholic fermentation while increasing the final acidity by lactic acid production. To properly assess the influence of this alternative strategy, we developed combined fermentations between specific strains of L. thermotolerans and S. pombe under sequential inoculation. Both species showed a great performance under the studied conditions, influencing not only the acidity but also the aromatic compound profiles of the resulting wines. The new proposed biotechnological strategy reduced the final concentrations of ethanol, malic acid and succinic acid, while it increased the concentrations of lactic acid and esters.